PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR SUBTEMA KEBERSAMAAN DALAM KEBERAGAMAN - Asofa Tanhara; Santa; Sri Rahayu Dwiastuti (STKIP Subang, 2023)
The approach taken is a quasi-experimental design of two groups at Situ Gede 2 State Elementary School. These subjects are students of class IV A and IV B of Situ Gede 2 State Elementary School, Bogor City, consisting of 64 students. This research was conducted in the odd semester of the 2021 academic year. /2022. The results of the study show that there is an effect of